Integrating Educational Management into Tuberculosis Control Program Implementation: A Strategy for Strengthening Primary Health Care Performance - Anjola, Anggun Febrika; Hanoselina, Yulia (Al-Qalam Institue, 2025)
This study analyzes the implementation of the Tuberculosis (TB) Control Program at Community Health Centers (Puskesmas) using George C. Edward III’s policy implementation model, which includes four key variables: communication, resources, disposition, and bureaucratic structure. Employing a descriptive qualitative approach through interviews, observations, and document analysis, the research found that the TB program has been implemented effectively, supported by clear national guidelines, standardized operating procedures, adequate laboratory facilities, and a well-functioning SITB reporting system. Strong commitment from program implementers further contributes to its success. However, several challenges persist, including limited human and financial resources, high staff workload, and suboptimal intersectoral coordination. From an educational management perspective, the study highlights the importance of strengthening capacity-building initiatives, continuous professional development, and leadership training among health workers to enhance program sustainability. Integrating management education principles—such as effective communication, collaborative leadership, and strategic planning—into public health practice can improve organizational performance and service delivery in primary care settings. This study contributes to bridging the gap between educational management and public health policy implementation, emphasizing the need for adaptive, learning-oriented management approaches to achieve long-term TB control goals in community-based health systems.